1997
DOI: 10.1074/jbc.272.52.33028
|View full text |Cite
|
Sign up to set email alerts
|

The Testis-specific Histone H1t Gene Is Strongly Repressed by a G/C-rich Region Just Downstream of the TATA Box

Abstract: H1t is a testis-specific histone 1 variant restricted to the male germ line and expressed only in pachytene spermatocytes. Understanding the regulation of the H1t gene is an interesting challenge as its promoter shares all of the recognized control elements of standard somatic H1 genes, yet H1t is not expressed in somatic or in early spermatogenic cells. To investigate the mechanism of this apparent repression, we exchanged three promoter subregions between H1t and a major somatic H1 gene (H1d) by introduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 53 publications
0
50
1
Order By: Relevance
“…To date, several genes showing testis-specific expression have been studied, including histone H1t [30,31], calmodulin gene II (CaMII) [32] and lactate dehydrogenase (LDHC) [33]. Transgenic studies showed that expression of the rat H1t gene was restricted (a) The presence of binding molecule(s) in the nuclear extract of L cells using CDPSE as probe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, several genes showing testis-specific expression have been studied, including histone H1t [30,31], calmodulin gene II (CaMII) [32] and lactate dehydrogenase (LDHC) [33]. Transgenic studies showed that expression of the rat H1t gene was restricted (a) The presence of binding molecule(s) in the nuclear extract of L cells using CDPSE as probe.…”
Section: Discussionmentioning
confidence: 99%
“…Given the importance of promoters in the expression of a variety of testisspecific genes [30][31][32][33], we focused on the 5h-flanking region of murine CD46 to determine the regulatory mechanisms governing its expression. Primer-extension analysis with the primer pr-1, a 35-mer corresponding to a portion of the signal peptide of murine CD46 revealed a major transcription start point, at 171 bp upstream of the Met start codon (Figure 1a and 1b).…”
Section: Analyses Of the 5h-flanking Region Of The Murine Cd46 Genementioning
confidence: 99%
“…Sequences in this region have been described previously as negative regulators of testis-specific genes including the rat sperm H2B gene and the rat H1t genes (22,23). In these cases the protein binding these sites was not identified.…”
Section: Discussionmentioning
confidence: 99%
“…The testis-specific histone H1t gene is also expressed only in pachytene spermatocytes. A negative regulatory region designated GC box 2 lies just downstream of the TATA box and plays a major role in gene repression (23). The Sp1 proteins bind weakly to this element but are not involved in repression of this gene.…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of germcell-specific genes via the suppression of their transcription in somatic cells is a recurring theme in mammalian systems. (62)(63)(64) For example, histone variants that are expressed during mammalian spermatogenesis are subject to negative regulation in somatic cells. (62)(63)(64) Significant numbers of genes appear to be expressed in the male germ line of flowering plants, and it is likely that some of these genes are regulated by a mechanism other than repressor-controlled negative regulation.…”
Section: Grsf (Germline Restrictivementioning
confidence: 99%